Music, consumption and cultural critique: Towards a historical and theoretical framework for the study of festivals in Latin America (1990-2020) (Revista Argentina de Musicología, 2020)
The following article explains the importance of cultural and musical festivals in Latin America after the end of the period of dictatorships. The text proposes a historical and theoretical framework for the study of festivals in the Portuguese and Spanish-speaking regions, with the aim of contributing to the consolidation of this subfield as an object of study in musical research. First, I offer a genealogy of the concepts of “festival” and “fiesta”. Then, I describe what I consider the approaches to and themes of this phenomenon and how it has been studied in the world. In a third part, I analyze music festivals in terms of their musical/cultural actors, globalization processes and forms of participation. Later, I expound how cultural and musical festivals have been studied in Latin America, to finally offer some basic conclusions. As a final point, I propose that festivals are a legitimate object of study with an increasing interest worldwide and the future of which is promising in the light of current research, especially within the field of musical studies.
Keywords: festival; music; consumption; culture; Latin America